Condition assessment of high voltage insulation in power system equipment - James, R. E. (Institution of Engineering and Technology, 2008)
Annotation includes analyses of some of the insulation fault scenarios that may occur in power equipment n comprehensive coverage of fault investigations, maintenance requirements, insulation testing and condition monitoring.
Keywords: Electric insulators and insulation -- Testing.; High voltages.; elektronické knihy; electronic books